Rapamycin regulates Stearoyl CoA Desaturase 1 Expression in Breast Cancer - Luyimbazi, David (2010)
mTOR (mammalian target of rapamycin) signaling is a central regulator of protein translation, cell growth and metabolism. Alterations of the mTOR signaling pathway are common in cancer, making mTOR a promising therapeutic target. In clinical trials, rapamycin analogs have shown modest response rates for most cancer types, including breast cancer. Therefore, there is an urgent need to better understand rapamycin’s mechanism of action, in order to improve patient selection and to monitor pathway inhibition. To identify novel pharmacodynamic markers of rapamycin activity, we performed transcriptional profiling of total and polysome-associated RNA in three breast cancer cell lines representing different subtypes. In all three cell lines, we found that rapamycin significantly decreased polysome-associated mRNA for stearoyl-CoA desaturase 1 (SCD1), the rate-limiting enzyme in monounsaturated fatty acid synthesis. Activators of mTOR increased SCD1 protein expression, while rapamycin, LY294002 and BEZ235 decreased SCD1 protein expression. Rapamycin decreased total SCD1 RNA expression without inducing a significant decline in its relative polysomal recruitment (polysome/total ratio). Rapamycin did not alter SCD1 mRNA stability. Instead, rapamycin inhibited SCD1 promoter activity and decreased expression of mature transcription factor sterol regulatory element binding protein 1 (SREBP1). Eukaryotic initiation factor 4E (eIF4E) siRNA decreased both SCD1 and SREBP1 expression, suggesting SCD1 may be regulated through the mTOR/eIF4E-binding protein 1 axis. Furthermore, SCD1 siRNA knockdown inhibited breast cancer cell growth, while over-expression increased growth. Taken together these findings demonstrate that rapamycin decreases SCD1 expression, establishing an important link between cell signaling and cancer cell fatty acid synthesis and growth.